Changes in personnel policies of enterprises conditioned by the identification of knowledge workers = Zmiany w politykach personalnych przedsiębiorstw uwarunkowane identyfikacją pracowników wiedzy - Igielski, Michał (Zielona Góra: Faculty of Economics and Management Press)
The twenty-first century requires enterprises to change in their functioning, since management has been faced with an unprecedented challenge so far ? it is the result of a turbulent external environment. Due to transformations the companies cannot continue to build their competitive advantages based on investments in tangible resources and cheap labour.
Keywords: polityka personalna; pracownik wiedzy; konkurencyjność; przedsiębiorstwo; personnel policy; knowledge worker; competitiveness; enterprises